LEGAL IMPLICATIONS OF THE ALLOCATION OF THE BURDEN OF PROOF IN TAX AUDIT PROCEDURES INVOLVING FICTITIOUS TRANSACTIONS - Escalante Miñano, María (2025)
Non-real transactions (fictitious or simulated operations) are a significant form of tax evasion in Peru’s Value Added Tax system, involving invoices or transactions that never actually occurred. This article examines the legal implications of the burden of proof in tax audit procedures aimed at uncovering such sham transactions. A comparative analysis is conducted between Peruvian law and the frameworks of Spain, Chile, the United States, and Argentina, reviewing tax rules and evidence provisions, applicable legal principles, and the doctrine of dynamic burden of proof. The research finds that, across these jurisdictions, the obligation to prove the reality of transactions or entitlement to tax benefits lies primarily with the taxpayer, yet important differences and exceptions exist. We discuss how each system allocates or shifts the evidentiary burden – for instance, Spain’s General Tax Law explicitly places the onus on whoever claims a tax right, Chile’s Tax Code requires taxpayers to substantiate the truth of their returns, U.S. law allows shifting the burden to the IRS under certain conditions, and Argentina employs legal presumptions favoring the Treasury. The concept of a dynamic burden of proof is explored as a tool to assign proof duties to the party best positioned to produce evidence. In conclusion, the paper highlights the need for clearer regulation in Peru regarding the burden of proof in tax audits for non real operations, informed by comparative insights to ensure fairness, respect for taxpayer rights, and effective tax enforcement.Keywords: burden of proof, tax Audit, fictitious transactions, dynamic evidence, comparative law.